The long-term effects of early sports selection - Adrian Mehic (Research Institute of Industrial Economics (IFN), 2024)
This paper examines the long-term effects of early sports selection using a regression discontinuity design. I show that Swedish track and field athletes who qualified for a one-time appearance with the junior national team at age 17 are less likely to quit sports and more likely to improve their performance. Several years later, although few make a living from sports, selected athletes have earned more college credits and are more successful on the marriage market. I show that early sports selection fosters grit and resilience, leading to lower dropout rates and positive spillovers in other areas of life.
Keywords: I12; J24; L83; Z13; Z22; 330; Sports; Skills; Human capital formation; Academic outcomes; Marriage market